2015
DOI: 10.5603/fm.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Infraorbital groove localisation for the endoscopic decompression of the orbit in Graves’ disease

Abstract: Background:The aim of our study was to determine the localisation of the inferior margin of the optic canal in relation to the infraorbital canal/groove complex (IOC/G complex) 23.69 ± 2.80 mm; 36.75 ± 5.10 mm; 46.84 ± 3.24 mm, respectively. Conclusions: The presented measurements may be particularly helpful for endoscopic decompression in patients with the thyroid ophthalmopathy to avoid the complications. (Folia Morphol 2015; 74, 1: 78-83)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Lantos et al [41] reported a high risk of ION injury in maxillary sinus with chronic inflammation, neoplasms, and patients with these variations in resection of an inverted papilloma require an antral punch to introduce a balloon dilation catheter to approach the maxillary infundibulum. A window is opened through the gingivobuccal sulcus in the anterior wall of the maxilla to reach maxillary sinus in Caldwell Luc operation, which is one of the preferred methods in various situations such as chronic rhinosinusitis, paranasal papilloma and foreign body removal [8,9,11,56]. For these reasons, the variations of IOC in the maxillary sinus should be considered in the surgical procedures.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 99%
See 1 more Smart Citation
“…Lantos et al [41] reported a high risk of ION injury in maxillary sinus with chronic inflammation, neoplasms, and patients with these variations in resection of an inverted papilloma require an antral punch to introduce a balloon dilation catheter to approach the maxillary infundibulum. A window is opened through the gingivobuccal sulcus in the anterior wall of the maxilla to reach maxillary sinus in Caldwell Luc operation, which is one of the preferred methods in various situations such as chronic rhinosinusitis, paranasal papilloma and foreign body removal [8,9,11,56]. For these reasons, the variations of IOC in the maxillary sinus should be considered in the surgical procedures.…”
Section: The Angle Between the Ioc And The Axial Planementioning
confidence: 99%
“…It is known that ION paraesthesia may occur after surgical interventions [4,54]. Bilateral ION blockage is a preferred local method for early repair of cleft lip, facial lacerations, rhinoplasty repair and endoscopic endonasal maxillary sinus surgeries [13,31,35,48,56]. It is important to know the IOF neighbourhood for reducing complications in placement of malar, submalar, or paranasal implants [61].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] The endoscopic approach allows surgeons to perform complete medial orbital wall decompression with excellent visualization of the key landmarks. [ 16 ] In a study by Baradaranfar and Dabirmoghaddam, the authors achieved an excellent results with an average retro displacement of 4.1 mm by endoscopic orbital decompression. [ 14 ] They also concluded that patients undergoing orbital decompression should be informed about the possibility of postoperative diplopia which usually resolves on its own.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 ] The IOC/G complex is the pathway for the infraorbital bundle, and it is an important landmark in endoscopic transnasal decompression for the thyroid ophthalmopathy and other maxillofacial techniques. [ 16 ] In a recent study by Przygocka et al ., the authors tried to evaluate the morphometric measurements of various anatomical orbital parameters. They found out that the mean distance from the inferior margin of the optic canal to: The posterior margin of the infraorbital groove measured at its medial border (designated as OC-S); to the posterior margin of the roof of IOC (designated as OC-C); and to the zygomaticoorbitale (designated as OC-ZO) on the right side were: 23.41 ± 3.10 mm; 34.44 ± 5.30 mm; and 47.53 ± 4.13 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation